To complete the table of values for the function \( y = x^3 - 2 \), we will calculate \( y \) for each value of \( x \) provided.
Let's calculate the values step by step:
-
For \( x = -3 \): \[ y = (-3)^3 - 2 = -27 - 2 = -29 \]
-
For \( x = -2 \): \[ y = (-2)^3 - 2 = -8 - 2 = -10 \]
-
For \( x = -1 \): \[ y = (-1)^3 - 2 = -1 - 2 = -3 \]
-
For \( x = 0 \): \[ y = (0)^3 - 2 = 0 - 2 = -2 \]
-
For \( x = 1 \): \[ y = (1)^3 - 2 = 1 - 2 = -1 \]
-
For \( x = 2 \): \[ y = (2)^3 - 2 = 8 - 2 = 6 \]
-
For \( x = 3 \): \[ y = (3)^3 - 2 = 27 - 2 = 25 \]
Now, we can fill in the table:
| \( x \) | \( y \) | |-----------|-----------| | -3 | -29 | | -2 | -10 | | -1 | -3 | | 0 | -2 | | 1 | -1 | | 2 | 6 | | 3 | 25 |
Here is the completed table of values.